2012
DOI: 10.1051/0004-6361/201118315
|View full text |Cite
|
Sign up to set email alerts
|

Five-year optical and near-infrared observations of the extremely slow nova V1280 Scorpii

Abstract: We present optical (B, V, R c , I c and y) and near-infrared (J, H, and K s ) photometric and spectroscopic observations of a classical nova V1280 Scorpii for five years from 2007 to 2011. Our photometric observations show a declining event in optical bands shortly after the maximum light, which took about 250 days to recover. This event was most probably caused by dust formation. The event was accompanied by a short (∼30 days) re-brightening episode (∼2.5 mag in V), which suggests that there had been some re-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 38 publications
1
43
0
2
Order By: Relevance
“…Based on an estimate of the total dust mass formed during the 250 days after outburst, Chesneau et al (2008) suggested that a mass as large as 10 −4 M was ejected. Naito et al (2012) provided an independent estimate from neutral oxygen lines that confirmed the high mass ejected, an additional argument for a low-mass WD progenitor, known to statistically eject more mass that fast, massive ones. The interferometric observations also provided a consistent picture of the expansion rate in the plane of the sky estimated at 0.35 mas/d.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Based on an estimate of the total dust mass formed during the 250 days after outburst, Chesneau et al (2008) suggested that a mass as large as 10 −4 M was ejected. Naito et al (2012) provided an independent estimate from neutral oxygen lines that confirmed the high mass ejected, an additional argument for a low-mass WD progenitor, known to statistically eject more mass that fast, massive ones. The interferometric observations also provided a consistent picture of the expansion rate in the plane of the sky estimated at 0.35 mas/d.…”
Section: Introductionmentioning
confidence: 82%
“…The classical nova V1280 Sco was discovered in outburst by Yamaoka et al (2007) on 2007 February 04.86 (JD = 2 454 136.85), about 12 days before reaching its maximum in visual light (m V ∼ 4) and formed dust only two weeks after reaching maximum in visible (Das et al 2008). This nova experienced one of the slowest evolutions historically reported and the nebular phase was entered about 50 months (t ∼ 1600 d) after outburst (Naito et al 2012). This is a clear indication that the mass of the erupting WD is low (i.e.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The majority of the selected novae are classified as fast or very fast novae, with one exception: Nova Sco 2007 (V1280 Sco). The actual decay time of this nova is uncertain due to the massive dust formation in the early phase of the outburst (Naito et al 2012), but it is considered a slow nova. Therefore it is possible that the presence of the transient narrow emission line component was related to the speed class.…”
Section: Discussionmentioning
confidence: 99%